2021
DOI: 10.1101/2021.11.14.468537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral E Protein Neutralizes BET Protein-Mediated Post-Entry Antagonism of SARS-CoV-2

Abstract: SUMMARYInhibitors of Bromodomain and Extra-terminal domain (BET) proteins are possible anti-SARS-CoV-2 prophylactics as they downregulate angiotensin-converting enzyme 2 (ACE2). Here, we show that BET proteins should not be inactivated therapeutically as they are critical antiviral factors at the post-entry level. Knockouts of BRD3 or BRD4 in cells overexpressing ACE2 exacerbate SARS-CoV-2 infection; the same is observed when cells with endogenous ACE2 expression are treated with BET inhibitors during infectio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Moreover, BRD4 displays direct antiviral properties, including inhibition of HIV Tat antigen, hence viruses must neutralize this protein to thrive ( Wang et al, 2020 ; Alamer et al, 2021 ; Xu X. et al, 2021 ; Table 1 ). Indeed, several viruses, including HIV and SARS-CoV-2 have developed the ability to usurp BRD4, overcoming nutritional immunity ( Chen I. P. et al, 2021 ). For example, the E (envelope) protein of SARS-CoV-2 virus inhibits BRD4, neutralizing the function of this epigenetic reader ( Gordon et al, 2020 ).…”
Section: The Brd4/mir-29 Compensatory Systemmentioning
confidence: 99%
“…Moreover, BRD4 displays direct antiviral properties, including inhibition of HIV Tat antigen, hence viruses must neutralize this protein to thrive ( Wang et al, 2020 ; Alamer et al, 2021 ; Xu X. et al, 2021 ; Table 1 ). Indeed, several viruses, including HIV and SARS-CoV-2 have developed the ability to usurp BRD4, overcoming nutritional immunity ( Chen I. P. et al, 2021 ). For example, the E (envelope) protein of SARS-CoV-2 virus inhibits BRD4, neutralizing the function of this epigenetic reader ( Gordon et al, 2020 ).…”
Section: The Brd4/mir-29 Compensatory Systemmentioning
confidence: 99%
“…Chen et.al. showed that the viral protein E in its acetylated form can directly bind to the second bromodomain of BRD4, and it has evolved to antagonise interferon responses via inhibition of BET proteins (66).…”
Section: Discussionmentioning
confidence: 99%